Therapeutic genome engineering via CRISPR‐Cas systems. (15th February 2017) - Moreno, Ana M.; Mali, Prashant
Abstract : Differences in genomes underlie most organismal diversity, and aberrations in genomes underlie many disease states. With the growing knowledge of the genetic and pathogenic basis of human disease, development of safe and efficient platforms for genome and epigenome engineering will transform our ability to therapeutically target human diseases and also potentially engineer disease resistance. In this regard, the recent advent of clustered regularly interspaced short palindromic repeats (CRISPR)–CRISPR‐associated (Cas) RNA‐guided nuclease systems have transformed our ability to target nucleic acids. Here we review therapeutic genome engineering applications with a specific focus on the CRISPR‐Cas toolsets. We summarize past and current work, and also outline key challenges and future directions. WIREs Syst Biol Med 2017, 9:e1380. doi: 10.1002/wsbm.1380 This article is categorized under: Laboratory Methods and Technologies > Genetic/Genomic Methods Translational, Genomic, and Systems Medicine > Therapeutic Methods Abstract : Schematic of in vivo and ex vivo gene therapy modalities. In vivo gene therapy involves the direct intra‐tissue or systemic injection of delivery agents, followed by assaying of targeting efficacy with close monitoring of safety and efficacy of treatment. In this regard, re‐administration of delivery agents might be necessary to achieve therapeutic efficacy. A patient might also be treated via ex vivo gene therapy, where patient somatic cells are isolated and either (1) reprogrammed into patient‐specific iPSCs, followed by gene therapy of these cells, and which are then differentiated into specific tissue types and cell lineages for transplantation; or (2) edited via ex vivo culture coupled with gene therapy (for instance in HSCs).